2016
DOI: 10.3390/en9080588
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Fracturing Network Propagation in Random Naturally Fractured and Laminated Block Experiments

Abstract: Abstract:Researchers have recently realized thatsilty laminas are very developed in naturally fractured continentalsedimentary formations in the Ordos Basin(China). Studies have shown that silty laminas are significant to improve the physical properties and gas storage capacity, and the natural fractures interact with the hydraulic fractures to maximize the fracture network during hydraulic fracturing. However, the influence of silty laminas withrandom fractures on the created hydraulic fracture networkis not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 31 publications
(34 reference statements)
4
9
0
Order By: Relevance
“…Morphology of the fracture surfaces was obtained through the 3D scanner, and Figure 7 shows the reconstructed fracture surfaces based on the scanning data. The parameter of the Area Ratio (AR) was calculated to describe the roughness of fracture surfaces quantitatively, which is defined as the ratio of actual contact area to projected area of the main fracture surface [25]. The actual area of the fracture can be calculated by the reconstructed fracture surface, and the projected area is the cross-sectional area of each specimen core minus the borehole area.…”
Section: Geofluidsmentioning
confidence: 99%
“…Morphology of the fracture surfaces was obtained through the 3D scanner, and Figure 7 shows the reconstructed fracture surfaces based on the scanning data. The parameter of the Area Ratio (AR) was calculated to describe the roughness of fracture surfaces quantitatively, which is defined as the ratio of actual contact area to projected area of the main fracture surface [25]. The actual area of the fracture can be calculated by the reconstructed fracture surface, and the projected area is the cross-sectional area of each specimen core minus the borehole area.…”
Section: Geofluidsmentioning
confidence: 99%
“…In recent years, stimulated reservoir volume (SRV) fracturing has become the most efficient technology in tight reservoir formation treatment [8][9][10][11][12][13][14][15]. To enhance well production as much as possible, it is necessary to create complex fracture networks with a multiporosity medium by connecting hydraulic fractures with natural fractures away from the well bore, and then increasing the contact area with formations and reservoir stimulated volume [16][17][18][19][20][21][22][23]. Multiple porous media systems include network fractures, natural fractures, and matrix pore systems.…”
Section: Introductionmentioning
confidence: 99%
“…Preexisting fractures, whether naturally occurring or induced by human operations are the most rampant discontinuities, hence, easily encountered. Some studies (e.g., Dehghan et al, 2017, Zhang and Fan, 2016, Wang et al, 2016, Yushi et al, 2016, Hofmann et al, 2016, Tiegang et al, 2014, Chuprakov et al, 2013, Casas et al, 2006, have shown the intricate mechanisms that govern interactions between discontinuities and propagating hydraulic fractures. Analytical and numerical analyses have been employed by Chen et al (2016), Chuprakov et al (2013) and Dehghan et al (2017) to explore the crossing mechanism and the evolution of both hydraulic fracture geometry and injection pressure during interactions between hydraulic fractures and natural fractures.…”
Section: Introductionmentioning
confidence: 99%